Dielectric Properties, AC Conductivity, and Electric Modulus Analysis of Bulk Ethylcarbazole-Terphenyl - Abarkan, Mustapha; Bouachrine, Mohammed; Abdi, Farid; Naciri Bennani, Mohammed; Sadki, Hayat; Belghiti, Najat; Hadi, Nasr; Bouaamlat, Hussam; Lamcharfi, Taj-dine (Advances in materials science and engineering, 2020)
Electrical and dielectric properties for bulk ethylcarbazole-terphenyl (PEcbz-Ter) have been studied over frequency range 1 kHz–2 MHz and temperature range (R.T –120°C). The copolymer PEcbz-Ter was characterised by using X-ray diffraction. The frequency dependence of the dielectric constant (εr′) and dielectric loss (εr″) has been investigated using the complex permittivity. εr′ of the copolymer decreases with increasing frequency and increases with temperature. AC conductivity (σac) data were analysed by the universal power law. The behaviour of σac increases with increasing temperature and frequency. The change of the frequency exponent (s) with temperature was analysed in terms of different conduction mechanisms, and it was found that the correlated barrier-hopping model is the predominant conduction mechanism. The electric modulus was used to analyze the relaxation phenomenon in the material.